Nonlinear periodic foundations for seismic protection: Practical design, realistic evaluation and stability considerations. Issue 150 (November 2021) - Martakis, Panagiotis; Aguzzi, Giulia; Dertimanis, Vasilis K.; Chatzi, Eleni N.; Colombi, Andrea
Abstract: A comprehensive numerical study on the performance of a novel nonlinear foundation consisting of alternating layers of lead rubber bearings and concrete slabs is presented in this article. The novel design combines the established load bearing capacity of commercial bearings with wave propagation inhibition by means of Bragg scattering in periodic structures. This solution substantially reduces structural demand under ground motion excitation without compromising performance during operational loading. The performance of the foundation is evaluated through nonlinear response history analyses and it is compared against conventional base isolated alternatives. By explicitly simulating the hysteretic behaviour of lead rubber bearings, we demonstrate that the response complies with the best practice standard of current design codes, as defined for base-isolated buildings. A comparative study exposes the limitations of linear analysis, leading to unrealistic and non-conservative outcomes. The results reflect the superior performance of the novel foundation in reducing base displacements, owing to Bragg scattering, as well as its remarkable robustness to input and soil variability. A sensitivity analysis over the key design parameters provides valuable insights and enables tailoring the foundation to the dynamic characteristics of the supported structure. For the first time, a framework for the assessment of global stability is formulated and deployed, highlighting the importance of considering stability as a performance metric when designing layered periodic foundations. Highlights: Practical metafoundation design for low-rise buildings. Periodic metafoundation with layers of lead rubber bearings and concrete slabs. Global stability assessment for periodic metafoundations. Parametric analysis on metafoundation key parameters, soil and source variability.